2018
DOI: 10.1681/asn.2018050462
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Cerebral Blood Flow and Cognitive Function in Hemodialysis Patients

Abstract: Background The immediate and longer-term effects of hemodialysis on cerebral circulation, cerebral structure, and cognitive function are poorly understood.Methods In a prospective observational cohort study of 97 adults (median age 59 years) receiving chronic hemodialysis, we used transcranial Doppler ultrasound to measure cerebral arterial mean flow velocity (MFV) throughout dialysis. Using a well validated neuropsychological protocol, we assessed cognitive function during and off dialysis and after 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
122
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 39 publications
(39 reference statements)
16
122
3
2
Order By: Relevance
“…Higher tympanic temperature, ultrafiltration volume, ultrafiltration rate, and pH were significantly associated with a lower cerebral blood flow. A second study found similar results in a prospective, observational, cohort study of 97 adults, using transcranial Doppler ultrasound to measure cerebral arterial mean flow velocity throughout dialysis, with assessment of cognitive function during and off dialysis and after 12 months of treatment (2). Mean flow velocity declined significantly during dialysis, correlating with ultrafiltrate volumes and intradialytic decline in cognitive function, including verbal fluency and global and executive function.…”
Section: Answer: Dmentioning
confidence: 58%
“…Higher tympanic temperature, ultrafiltration volume, ultrafiltration rate, and pH were significantly associated with a lower cerebral blood flow. A second study found similar results in a prospective, observational, cohort study of 97 adults, using transcranial Doppler ultrasound to measure cerebral arterial mean flow velocity throughout dialysis, with assessment of cognitive function during and off dialysis and after 12 months of treatment (2). Mean flow velocity declined significantly during dialysis, correlating with ultrafiltrate volumes and intradialytic decline in cognitive function, including verbal fluency and global and executive function.…”
Section: Answer: Dmentioning
confidence: 58%
“…An alternative explanation may be related to the fact that conventional hemodialysis can cause recurrent acute cerebral ischemia [27]. Mark et al showed that patients undergoing hemodialysis experience transient declines in cerebral blood flow, correlating with intradialytic cognitive dysfunction [34], which in turn may contribute to a chronic decline in PM function. Additionally, small-vessel cerebrovascular disease is the most common cause of vascular dementia [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using neuropsychological tests and sophisticated tools (transcranial doppler ultrasonography, cerebral MRI) have identified a link between the deleterious effects of hemodialysis on cognitive function and changes in cerebral arterial flow velocity. 106,107 In a prospective observational cohort study of 97 adults receiving hemodialysis, the degree of decline in flow velocity in the middle cerebral arteries correlated with the decline in cognitive function. 107 Further, transient cognitive impairment has a negative impact on the patients' experience, but also on their health literacy and ability to process medical information, possibly affecting their ability to adhere to their treatment regimen.…”
Section: Cognitive Functionmentioning
confidence: 99%
“…106,107 In a prospective observational cohort study of 97 adults receiving hemodialysis, the degree of decline in flow velocity in the middle cerebral arteries correlated with the decline in cognitive function. 107 Further, transient cognitive impairment has a negative impact on the patients' experience, but also on their health literacy and ability to process medical information, possibly affecting their ability to adhere to their treatment regimen. Moreover, repetitive hemodialysis-induced brain insults may result in ischemic brain and white matter damage (leukoaraiosis) as shown in a prospective cerebral MRI study.…”
Section: Cognitive Functionmentioning
confidence: 99%